Enhanced synergistic effect of NiCo sulfide nanorod arrays with high mass loading on carbon cloth for hybrid supercapacitors: The role of compositional regulation - Chen, Lu; Chen, Shihuan; Chen, Gang; Deng, Jiahua; Xu, Xuetang; Wang, Fan (Journal of alloys and compounds, 2024)
Achieving an enhanced synergistic effect and controlling the morphology of active materials to facilitate electrolyte access are crucial for the design of high-mass-loading electrode. In this work, NiCo sulfide nanorod arrays were grown on a carbon cloth (CC) substrate via a two-step hydrothermal deposition strategy. The compositional effect was employed to modify the growth behavior, hierarchical morphology, and synergistic effect of the as-obtained electrodes. The contents of Ni-S and Co-S species and the resistance nature of the electrodes can be optimized by adjusting the Co/Ni feed ratio. The optimized Ni1.5Co1.5S4/CC electrode with a high mass loading (5.54 mg cm−2) comprises vertical nanorod arrays with open channels for electrolyte access, and exhibits a high capacity of 711 C g−1 at 2 A g−1 (3.95 C cm−2 at 10 mA cm−2) with good cyclic stability. The as-assembled Ni1.5Co1.5S4/CC//activated carbon cloth (ACC) hybrid supercapacitor delivers a high areal capacity of 1.96 C cm−2 at 5 mA cm−2 with excellent rate performance and achieves a high energy density of 0.49 mWh cm−2 at a power density of 4.5 mW cm−2. These achievements represent a promising concept for the practical design and regulation of NiCo sulfide electrodes at high mass loading levels. [Display omitted] •Structural and capacitive role of Ni and Co cations in NiCo sulfide nanoarrays.•Bimetallic synergistic effect is identified with compositional effect.•Vertical nanorod alignment of NiCo sulfide electrode with high mass loading.•Optimized Ni1.5Co1.5S4/CC electrode shows the capacity 3.95 C cm−2 at 10 mA cm−2.